2017
DOI: 10.1177/1071100717723131
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Sole Release of the Plantar Fascia Combined With Percutaneous Drilling of the Calcaneus for Treatment of Resistant Heel Pain

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Open, mini-open, and arthroscopic plantar fasciotomy methods have been reported. The open plantar fascia release procedure is a popular method; however, it requires a large incision and significant dissection, the healing time is longer and there is the potential risk of painful scar tissue [1,21] . Arthroscopic plantar fascia release has been evaluated as a method with a high success rate by experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open, mini-open, and arthroscopic plantar fasciotomy methods have been reported. The open plantar fascia release procedure is a popular method; however, it requires a large incision and significant dissection, the healing time is longer and there is the potential risk of painful scar tissue [1,21] . Arthroscopic plantar fascia release has been evaluated as a method with a high success rate by experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…P ainful heel syndrome is characterized by pain and sensitivity in the inferomedial aspect of the calcaneal tuberosity. The incidence is approximately 15% in the adult population [1] . Although its etiology has not yet been completely clarified, plantar fasciitis is thought to be the most important cause of painful heel syndrome [2] .…”
mentioning
confidence: 99%
“…Retrospective evaluations of partial plantar fasciotomy have reported rates of success, ranging from 57% to 96%. 7,8,43,46,48 All of these studies have had substantial limitations and variability limiting any definitive conclusions on the benefit of operative release. Many of these studies report worsening and/or persistent heel pain in an unacceptably high percentage of patients.…”
Section: Partial Plantar Fasciotomymentioning
confidence: 99%
“…A number of retrospective reviews have demonstrated success with these techniques ranging from 40% to 100%, but none have demonstrated clear superiority over the open technique and they both have rates of persistent heel pain similar to open surgery. 5,6,25,38,43 It is often difficult to distinguish between PF and nerve compression. The history, physical examination, and imaging provide essential clues, but cannot always differentiate between them.…”
Section: Partial Plantar Fasciotomymentioning
confidence: 99%
“…Plantar fasciitis is the most common cause of chronic heel pain, affecting up to 15% of adult foot complaints. 25,29,33 It is usually a self-limiting disease as it usually resolves within 8-12 months in approximately 80% to 90% of patients. 14,27 However, it can be a challenging condition as several months to even years may be required before subsidence of symptoms with conservative treatment.…”
Section: Introductionmentioning
confidence: 99%